2014
DOI: 10.1111/iej.12273
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Fusobacterium nucleatum and Peptostreptococcus anaerobius DNA after loss of cell viability

Abstract: Amplifiable DNA from F. nucleatum and P. anaerobius was detectable 6 months after loss of viability. Air-killed anaerobes initially retained their cell form, but cells gradually shriveled over time. The morphological changes were more pronounced with the gram-negative F. nucleatum than the gram-positive P. anaerobius. Over 6 months, there was a gradual increase in cell wall permeability with progressive leakage of DNA. Bacterial DNA was recoverable long after loss of cell viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
5
12
0
3
Order By: Relevance
“…Our data support previous assertions that DNA from dead bacteria may be a potential confounder in endodontic microbiology studies, as they may overestimate the number of species identified in persistent endodontic infections. 17,18…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data support previous assertions that DNA from dead bacteria may be a potential confounder in endodontic microbiology studies, as they may overestimate the number of species identified in persistent endodontic infections. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborate previous in vitro data that showed that DNA may persist in infected teeth after bacterial death. 11,17,18 The high binding affinity between DNA and hydroxyapatite/dentin has been shown to make it less susceptible to degradation by serum and nucleases, contributing to long-term persistence of DNA in teeth. 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figura 5.2 -Níveis médios de rDNA e rRNA em amostras qPCR positivas para ambos os métodos após: cirurgia de acesso (S1), preparo químico-cirúrgico (S2), XPF (S3a), PUI (S3b), medicação intracanal entre sessões (S4) e repreparo dos canais radiculares (S5) (Brundin et al, 2015). Por outro lado, o uso do rRNA permite avaliar a viabilidade de bactérias por ser rapidamente degradado após a morte da célula.…”
Section: Taxas De Detecçãounclassified
“…Com intuito de contornar tal limitação deste procedimento molecular, foi proposta uma técnica que utiliza o corante etídio monoazida (EMA), que se liga quimicamente ao DNA de células com a membrana comprometida, o que impede sua amplificação por qPCR, e torna possível contabilizar apenas as células viáveis(43,78,82,85). Outro método molecular sugerido para detecção precisa de células viáveis, utiliza o corante propídio monoazida (PMA), que se liga de maneira covalente apenas ao DNA de bactérias com a membrana comprometida, desta forma, o qPCR amplificaria apenas as células viáveis da amostra analisada(43,78,(82)(83)(84)(85)(86). Este novo procedimento foi utilizado com sucesso em estudos de microbiologia(43,78,83,85), endodontia(84)e, o presente estudo propõe utilizá-lo na odontologia adesiva para mensurar de forma mais o efeito de antimicrobianos.…”
unclassified